Isoform-specific disruption of the TP73 gene reveals a critical role for TAp73γ in tumorigenesis via leptin - Xiangmudong Kong; Wensheng Yan; Wenqiang Sun; Yanhong Zhang; Hee Jung Yang; Mingyi Chen; Hongwu Chen; Ralph W de Vere White; Jin Zhang; Xinbin Chen (eLife, 2023)
TP73, a member of the p53 family, is expressed as TAp73 and ΔNp73 along with multiple C-terminal isoforms (α−η). ΔNp73 is primarily expressed in neuronal cells and necessary for neuronal development. Interestingly, while TAp73α is a tumor suppressor and predominantly expressed in normal cells, TAp73 is found to be frequently altered in human cancers, suggesting a role of TAp73 C-terminal isoforms in tumorigenesis. To test this, the TCGA SpliceSeq database was searched and showed that exon 11 (E11) exclusion occurs frequently in several human cancers. We also found that p73α to p73γ isoform switch resulting from E11 skipping occurs frequently in human prostate cancers and dog lymphomas. To determine whether p73α to p73γ isoform switch plays a role in tumorigenesis, CRISPR technology was used to generate multiple cancer cell lines and a mouse model in that Trp73 E11 is deleted. Surprisingly, we found that in E11-deificient cells, p73γ becomes the predominant isoform and exerts oncogenic activities by promoting cell proliferation and migration. In line with this, E11-deficient mice were more prone to obesity and B-cell lymphomas, indicating a unique role of p73γ in lipid metabolism and tumorigenesis. Additionally, we found that E11-deficient mice phenocopies Trp73-deficient mice with short lifespan, infertility, and chronic inflammation. Mechanistically, we showed that Leptin, a pleiotropic adipocytokine involved in energy metabolism and oncogenesis, was highly induced by p73γ,necessary for p73γ-mediated oncogenic activity, and associated with p73α to γ isoform switch in human prostate cancer and dog lymphoma. Finally, we showed that E11-knockout promoted, whereas knockdown of p73γ or Leptin suppressed, xenograft growth in mice. Our study indicates that the p73γ-Leptin pathway promotes tumorigenesis and alters lipid metabolism, which may be targeted for cancer management.